Comparison of the Effectiveness of Circuit Weight Training and Aerobic Exercise on Reducing Body Fat Percentage and Body Mass Index in Women - Moh Muhaemin Yusup; Naufal Juhan Daiva; Muhammad Fikri Hanif; M. Arief Setiawan; A. Ine Aprilia Damai; Aprillia Wulan Utari (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2026)
The increasing prevalence of overweight and obesity has become a global health problem closely related to a sedentary lifestyle and energy imbalance. Controlling body composition, particularly body fat percentage and Body Mass Index (BMI), requires effective interventions based on physical activity. This study aimed to compare the effectiveness of Circuit Weight Training (CWT) and aerobic exercise on reducing body fat percentage and BMI. The method used was a quasi-experimental design with a two-group pretest-posttest approach. The research sample consisted of 30 women categorized as overweight to obese, divided into two groups: the CWT group and the aerobic exercise group. The intervention was carried out for 8 weeks with a frequency of three sessions per week. Instruments used included Bioelectrical Impedance Analysis (BIA) to measure body fat percentage, along with height and weight measurements to determine BMI. Data analysis used paired sample t-test and independent sample t-test. The results showed that both exercise methods had a significant effect on reducing body fat percentage and BMI (p < 0.05). However, the CWT group showed a greater reduction in body fat percentage (-5.35%) compared to the aerobic group (-3.13%), as well as a greater decrease in BMI (-2.25 compared to -1.45). The discussion indicates that the effectiveness of CWT was influenced by the combination of resistance and cardio training, which increases metabolism and the EPOC effect, resulting in more optimal fat burning.